2005
DOI: 10.1103/physrevb.72.045447
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and separation of linear and branched alkanes on carbon nanotube bundles from configurational-bias Monte Carlo simulation

Abstract: The adsorption and separation of linear ͑C 1 -nC 5 ͒ and branched ͑C 5 isomers͒ alkanes on single-walled carbon nanotube bundles at 300 K have been studied using configurational-bias Monte Carlo simulation. For pure linear alkanes, the limiting adsorption properties at zero coverage exhibit a linear relation with the alkane carbon number; the long alkane is more adsorbed at low pressures, but the reverse is found for the short alkane at high pressures. For pure branched alkanes, the linear isomer adsorbs to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
97
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 109 publications
(106 reference statements)
14
97
0
Order By: Relevance
“…Note that both, the chain length dependency of the Henry coefficients and the chain length dependency of the heats of adsorption were also observed experimentally for alkanes in zeolites [40]. Furthermore, these dependencies were already observed with molecular simulation methods for the adsorption of alkanes in CNT bundles [4] and, in agreement with experiments, for the adsorption in silicalite [20,41].…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Note that both, the chain length dependency of the Henry coefficients and the chain length dependency of the heats of adsorption were also observed experimentally for alkanes in zeolites [40]. Furthermore, these dependencies were already observed with molecular simulation methods for the adsorption of alkanes in CNT bundles [4] and, in agreement with experiments, for the adsorption in silicalite [20,41].…”
Section: Resultssupporting
confidence: 72%
“…These maxima were also observed by Jiang et al [4] and Heyden et al [22] for carbon nanotubes and by Jakobtorweihen et al [24] for zeolites, among others. Note that Jiang et al [4] have also observed distinct maxima in the selectivities for mixtures of C5 isomers. The selectivity drops from about two at low pressures to about one at high pressures.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Thus far, only a few studies deal with the behavior of alkanes in nanotubes. [34][35][36][37][38][39][40][41][42][43][44] Further, Wei and Srivastava 20 investigated the behavior of polymers in CNTs.…”
Section: Introductionmentioning
confidence: 99%